THE PROCESS OF COORDINATION IN THE AGROINDUSTRIAL SYSTEM OF SPECIALTY COFFEE - Barra, Geraldo Magela Jardim (Informe GEPEC, 2018)
The associations are important to support farmers who wish to trade on agroindustrial systems, playing a coordinating officer role. Due to the increasing number of associations in the agroindustrial system of specialty coffee in Brazil, demand is created by studies that describe the role of these associations in support of the business of its members. It has developed as a general goal, describe and analyze the role of a growers association in supporting the business of Brazilian producers of specialty coffees. We conducted a case study that examined both the influence of the actions of this association in the affairs of its members as externalities generated to Brazilian producers of specialty coffees. It appears that the organization studied is evidence of an important coordinating officer to support businesses in agribusiness systems. The findings of the study ratify the theory that this type of organization contributes to the buildup of trust among partners, lessens information asymmetry and reduces transaction costs.